Differences Between Online Trial Participants Who Have Used Statutory Mental Health Services and Those Who Have Not: Analysis of Baseline Data From 2 Pragmatic Trials of a Digital Health Intervention - Stefan Rennick-Egglestone; Chris Newby; Clare Robinson; Caroline Yeo; Fiona Ng; Rachel A Elliott; Yasmin Ali; Joy Llewellyn-Beardsley; Scott Pomberth; Julian Harrison; Sean P Gavan; Pim Cuijpers; et al. (JMIR Publications, 2023)
BackgroundDigital health interventions (DHIs) are an established element of mental health service provision internationally. Regulators have positioned the best practice standard of evidence as an interventional study with a comparator reflective of standard care, often operationalized as a pragmatic trial. DHIs can extend health provision to those not currently using mental health services. Hence, for external validity, trials might openly recruit a mixture of people who have used mental health services and people who have not. Prior research has demonstrated phenomenological differences in mental health experience between these groups. Some differences between service users and nonservice users might influence the change created by DHIs; hence, research should systematically examine these differences to inform intervention development and evaluation work. This paper analyzes baseline data collected in the NEON (Narrative Experiences Online; ie, for people with experience of psychosis) and NEON-O (NEON for other [eg, nonpsychosis] mental health problems) trials. These were pragmatic trials of a DHI that openly recruited people who had used specialist mental health services and those who had not. All participants were experiencing mental health distress. NEON Trial participants had experienced psychosis in the previous 5 years. ObjectiveThis study aims to identify differences in baseline sociodemographic and clinical characteristics associated with specialist mental health service use for NEON Trial and NEON-O Trial participants. MethodsFor both trials, hypothesis testing was used to compare baseline sociodemographic and clinical characteristics of participants in the intention-to-treat sample who had used specialist mental health services and those who had not. Bonferroni correction was applied to significance thresholds to account for multiple testing. ResultsSignificant differences in characteristics were identified in both trials. Compared with nonservice users (124/739, 16.8%), NEON Trial specialist service users (609/739, 82.4%) were more likely to be female (P<.001), older (P<.001), and White British (P<.001), with lower quality of life (P<.001) and lower health status (P=.002). There were differences in geographical distribution (P<.001), employment (P<.001; more unemployment), current mental health problems (P<.001; more psychosis and personality disorders), and recovery status (P<.001; more recovered). Current service users were more likely to be experiencing psychosis than prior service users. Compared with nonservice users (399/1023, 39%), NEON-O Trial specialist service users (614/1023, 60.02%) had differences in employment (P<.001; more unemployment) and current mental health problems (P<.001; more personality disorders), with lower quality of life (P<.001), more distress (P<.001), less hope (P<.001), less empowerment (P<.001), less meaning in life (P<.001), and lower health status (P<.001). ConclusionsMental health service use history was associated with numerous differences in baseline characteristics. Investigators should account for service use in work to develop and evaluate interventions for populations with mixed service use histories. International Registered Report Identifier (IRRID)RR2-10.1186/s13063-020-04428-6